Driving Nonprofit Sustainability: Building Leadership Confidence Through Effective Decision-Making and Collaboration for Long-Term Success - Joseph, Paulraj (Digital Repository of Theses - SSBM Geneva, 2025)
Nonprofit organizations (NPOs) greatly contribute to advance social development by addressing some of the most urgent issues facing mankind, including poverty, inequality, and environmental destruction. Though their survival is a matter of importance and concern, this study addresses a basic question: under a period of rising crisis and limited resources, what factors enable the durability and success of these important organizations? Combining quantitative survey findings with in-depth qualitative insights from NPO executives utilizing a mixed-methods approach, this study brings to light the dynamics either supporting or damaging the viability of organizations. The results are shocking and urgently important. Mostly dependent on strong, adaptable leadership, organizations that endure and advance not simply to survive but also to be an agent that influences transformation. Strong organizational cultures which are ready to address difficulties will result from leaders who motivate their teams, build trust, operate ethically and clearly manage complexity. Moreover, it is important to have a cooperative nonprofit ecosystem through which, collaboration and shared resources and knowledge increase organization effectiveness. A synergetic nonprofit ecosystem helps mutually and results in cooperation instead of rivalry. The research shows how shortsighted decision-making, isolated operations, and low public confidence jeopardize the sector's future as well as provides solutions for these issues. The learnings beat complacency. Beyond basic financial viability, sustainability is really about preserving the mechanisms that champions social justice and social responsibility. Through bridging significant gaps in current research, the study provides leaders, policymakers, and communities with a strategic framework to reevaluate how the nonprofit sector functions in a society that faces a lot of challenges. Strong action is demanded through the recommendations: reinventing leadership models, creating technologically motivated collaborations, and including equity into all domains of organizational operations. Without complete transformation, nonprofits run the risk of becoming victims of the exact issues they aim to address. Leaders should act fearlessly; ecosystems should work with intent; and society should engage in major transformation. While this study’s regional sample and reliance on self-reported data invite further validation, its findings provide a critical foundation for redefining nonprofit resilience in this century.